The Role Of Zakat Distribution Among Muallaf (New Convert) In Reducing Poverty In Selangor, Malaysia - Fuadah Johari; Muhammad Ridhwan Ab. Aziz; Ahmad Fahme Mohd Ali (Istanbul University, 2024)
İktisat Politikası Araştırmaları Dergisi Journal of Economic Policy Researches Cilt/Volume:2, Sayı/Issue:1, Yıl/Year: 2015, 39-56